Implementation of student-centred teaching at the International Islamic University Malaysia (IIUM) and students' attitute towards it - Olasunkanmi, Abdulhameed Kamoludeen (Kulliyyah of Education, International Islamic University Malaysia, 2016)
The purpose of this study is to investigate the perception and attitude of students towards the implementation of student-centred teaching (SCT) in the International Islamic University Malaysia (IIUM). This investigation will determine whether it reflects the SCT approach required by the Malaysian Qualification Agency (MQA) under the Ministry of Higher Education Malaysia (MOHEM). It then explores the significant differences among IIUM kulliyyahs (faculties), gender, level of students and their nationality with regards to their perception and attitude towards SCT. The relationship between IIUM students' perception and attitude towards SCT was also examined in this study. In this cross sectional study, 243 students were surveyed from all eight Kulliyyahs (Faculties) located in the Gombak campus. The questionnaires and the quantitative data collected in this study were analyzed using descriptive and inferential (ANOVA, INDEPENDENT SAMPLE T-TEST, CORRELATION and REGRESSION) statistical procedures. The findings of the study indicated that IIUM students hold a fairly positive perception and attitude towards SCT with mean scores of 3.71 and 3.97 out of the maximum score of 5.00 respectively. This implies that IIUM lecturers are implementing SCT approach to a certain extent. The results also revealed that there is a significant difference between Ahmad Ibrahim Kulliyyah of Law (AIKOL) and Kulliyyah of Engineering (KOE) in terms of students' perception on SCT. There was however a significant difference between IIUM male and female students with respect to their perception but not attitude towards SCT. Additionally, IIUM postgraduate and undergraduate students showed no significant difference in perception but not their attitude towards SCT. Consequently, Malaysian students showed better perception on SCT compared to their international counterparts, while international students had better attitude towards SCT compared to their Malaysian colleagues. Finally, the findings also showed that there was a positive significant relationship between perception and attitude of students towards SCT which indicated that students' perception was a reasonable predictor for their attitude towards SCT. This study therefore, found that SCT approach is being implemented in the IIUM community and recommended further studies on the paradigm.